2016
DOI: 10.1007/s11999-016-4860-x
|View full text |Cite
|
Sign up to set email alerts
|

Are Females at Greater Risk for Revision Surgery After Hip Resurfacing Arthroplasty With the Articular Surface Replacement Prosthesis?

Abstract: Background Female patients undergoing hip resurfacing arthroplasties may be at greater risk of revision surgery than males, but it is unclear whether this is related to sex or other factors. We focused our analysis on data from a prospective multicenter cohort study monitoring the ASR TM hip resurfacing arthroplasty prosthesis on the potential association of sex on patient-reported outcome measures (PROMs), metal ion levels, revision surgery, and presence of adverse local tissue reaction. As thousands of patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 35 publications
(45 reference statements)
1
7
0
Order By: Relevance
“…For women, the change was 2.7 ppb, and for men it was 0.5 ppb. This A disparity between the genders in the levels of Co ions has been confirmed by some authors 19,20 although there is some contradictory evidence. 18 No studies to our knowledge have reported a significant increase in the levels of Co ions over time for patients with a MoM HRA implant.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…For women, the change was 2.7 ppb, and for men it was 0.5 ppb. This A disparity between the genders in the levels of Co ions has been confirmed by some authors 19,20 although there is some contradictory evidence. 18 No studies to our knowledge have reported a significant increase in the levels of Co ions over time for patients with a MoM HRA implant.…”
Section: Discussionsupporting
confidence: 57%
“…The change for women was 1.0 ppb over two years, while for men it was only 0.3 ppb during this time. Several studies have shown a difference between the genders in levels of Cr ions at a single time point, [18][19][20] but none to our knowledge have shown such a difference in the later stages of follow-up. This finding is of particular interest in the light of recently published findings that women with increased level of Cr ions have worse health-related quality of life and hip function.…”
Section: Discussionmentioning
confidence: 74%
“…Details of this study are explained in previous literature. 12,13 BMI was not required data in the follow-up study of the ASR hip system but was reported nonetheless by many sites. We only included data from centres that reported BMI data on 90% or more of the patients in our analyses in order to eliminate selection bias.…”
Section: Methodsmentioning
confidence: 99%
“…These modalities include femoral head core decompression, osteotomy, electrical stimulation, and bone grafting with muscle-pedicle bone grafts, vascular-pedicle bone grafts, and free vascularized bone grafts [10,[19][20][21]. If hip joint reconstruction is deemed necessary, hip resurfacing (HR) and THA remain the primary treatment modalities [56][57][58][59][60][61]. HR has had poor results historically [56,61], but more recent studies using meticulous patient selection in young adults have demonstrated satisfactory short-to medium-term outcomes.…”
Section: Current Controversies and Future Considerationsmentioning
confidence: 99%
“…However, there is conflicting evidence regarding whether patients undergoing HR for femoral head ON have similar outcomes to those undergoing HR for osteoarthritis [21,62,63]. Furthermore, it is worth noting that females may be at increased risk of revision after HR [57,58]. With respect to pediatric THA, emerging evidence demonstrates favorable medium-to long-term outcomes when using cementless techniques and modern implant designs [12,38,[40][41][42].…”
Section: Current Controversies and Future Considerationsmentioning
confidence: 99%